Cost analysis for FGD units of coal-fired power plants: a case study in Turkey - Guney, Irfan; Kilic, Osman; Acarkan, Bora; Ay, Selim (SILA SCIENCE, 2012)
Electrical energy generation sector is expanding every year. Due to the increase in population and the developments in international interconnections, countries have started to consume and produce remarkable amounts of electricity. Coal-fired power plants take the highest share in electricity production. Therefore, emission reduction, especially for sulfur dioxide (SO2) is a must. Thermal power plants that use, domestic coal reserves with high sulfur content, must have Flue Gas Desulfurization (FGD) units. Sulfur dioxide emissions are reduced through FGD units, but this is an expensive process. FGD costs are generally analyzed on annual bases. This paper will introduce a new formulation for the hourly cost of a FGD unit, considering the fact that power plants' operational parameters might change on hourly bases. The followings are the parameters that might change on hourly bases; sulfur contents and calorific values of the coal arrived at the power plant in different lots, hourly energy sale rates and hourly loading rates. A novel cost analysis of the FGD unit is applied to the Orhaneli power plant (1x210 MW) and the results obtained by using four different discounting models are compared with the conventional annual cost analysis results.
Keywords: Discounted cost; Escalation; Flue gas desulfurization; Limestone; Power plant; Rated interest; SO2 control; ENVIRONMENTAL IMPACTS; REDUCTION; POLLUTION; DISPATCH; SYSTEM; Energy & Fuels; Engineering